Diversity in early care and education - Gonzalez-Mena, Janet
Diversity in Early Care and Education (formerly Multicultural Issues In Child Care) explores the rich diversity encountered in programs and environments for children ages birth to 8, including those serving children with special needs. The emphasis is on the practical and immediate concerns of the early childhood professional and family service worker, though all information has strong theoretical support